Repercussions in newborns infected by the new coronavirus during pregnancy: Integrative review (Research, Society and Development, 2021)
The aim of this study is to identify the evidence available in the literature about the repercussions on newborns of mothers infected with coronavirus during pregnancy. This is an integrative literature review, carried out from March to April 2021, in the Scientific Electronic Library Online (SciELO), Latin American Literature in Health Sciences (Lilacs) and Medical Literature Analysis and Retrieval System databases. Online (MEDLINE). The following descriptors were used: COVID-19, Pregnancy, Signs and Symptoms, Corona virus, Newborns, according to the classification of the Health Sciences Descriptors (DECS) and for each descriptor cited, the Boolean operator “AND ” and for synonyms the “OR” was used. Six articles from the MEDLINE database and 02 articles from the SCIELO database were selected to integrate this study, totaling 08 articles. Regarding the study design, 3 (30%) articles were integrative reviews and 5 (70%) were exploratory studies of the case study type. After reading and summarizing the data, two categories emerged, namely: Clinical manifestations in newborns diagnosed with COVID-19 and Repercussions of infection caused by SARS-CoV-2 in neonates. There was the possibility of identifying the symptoms presented by this clientele and the possible complications in cases aggravated by the infection. Based on this assumption, repercussions on newborns are still extremely scarce in the literature and the few studies that describe the possible repercussions bring only limited data on the impact of the current outbreak of COVID-19 on women affected during pregnancy and their newborns.